Monitoring Deteksi Kanker Payudara Berbasis Aplikasi Ca. Mammae Di Rumah Sakit Ibnu Sina Yw-UMI Kota Makassar - Dwita Ayu Israwati; Hasriwiani Habo Abbas; Arman (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Breast cancer is a disease of excessive growth or uncontrolled development of cells (tissue) in the breast. Breast cancer (Carcinoma Mammae) is defined as a malignant neoplasm originating from the parenchyma. This study aimed to determine the characteristics of breast cancer incidence at Ibnu Sina Hospital YW-UMI Makassar City as the basis for designing the Ca. Mammae application. This type of research uses quantitative research with a descriptive design. The population in this study was outpatients at Ibnu Sina Hospital, Makassar City. The sampling technique used was Accidental Sampling with a sample size of 155 people. The analysis method used univariate analysis to determine the characteristics of breast cancer. The results of this study obtained that breast cancer is the highest based on age at risk of 78.8%, the highest family history of breast cancer is 73.5%, the age of first menstruation based on the category of breast cancer risk is 50.3%, the highest age of first childbirth is the category of breast cancer risk of 80%, history of breastfeeding based on the category of not breastfeeding is 44.5%, the highest age of menopause is the category of breast cancer risk of 51%, parity based on the highest category is nilipara at 44.5%. In comparison, the category of primipara is 40%, and the use of hormonal contraception with the category of hormonal breast cancer is 54.8%. The application of sadari in the category of not applying is 80%. The conclusion of these results shows that there are characteristics of age, family history, age of first menstruation, age of first childbirth, history of breastfeeding, age of menopause, parity, use of hormonal contraception, and the application of Sadari.